Big push or big grab? Railways, government activism, and export growth in Latin America, 1865–1913 - Bignon, V; Ferreira Da Costa Esteves, R; Herranz-Loncán, A (Wiley, 2015)
Railways were one of the main engines of the Latin American trade boom before 1914. Railway construction often required financial support from local governments, which depended on their fiscal capacity. However, since the main government revenues were trade-related, this generated a two-way feedback between government revenues and railways, with a potential for multiple equilibria. The empirical tests in this article support the hypothesis of such a positive two-way relationship. The main implication of our analysis is that the build-up of state capacity was a necessary condition for railway expansion and also, to a large extent, for export expansion in Latin America during the first globalization.